Buckling and post-buckling analysis of FGM plates resting on the two-parameter Vlasov foundation using general third-order plate theory - Taczała, M.; Buczkowski, R.; Kleiber, M. (Archives of Mechanics, 2024)
We present a nonlinear finite element analysis to investigate the buckling and post-buckling behaviour of functionally graded material (FGM) plates resting on the elastic foundation. The material properties are assumed to vary gradually across the thickness according to a power law distribution. The starting point of the investigation is the generalized third-order plate theory and the Vlasov model of elastic foundation having properties varying throughout the depth. The plates are subjected to bending to verify the formulation and compression loads including buckling and post-buckling analysis to investigate the influence of various parameters on the structural response.